Peran Kepuasan Pengunjung Mall pada Pengaruh Positioning Mall terhadap Loyalitas Pengunjung Mall: Studi Kasus pada Pollux Mall Chadstone - Asral Asral; Syifa Ramadhani Asmi (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The background of this study is based on the importance of positioning strategy in the modern retail industry, especially in the shopping center sector, to increase competitiveness and maintain customer loyalty. This study aims to analyze the role of visitor satisfaction in mediating the influence of mall positioning on visitor loyalty at Pollux Mall Chadstone. The research method used is a quantitative approach with a survey technique through a questionnaire distributed to 200 respondents who have visited Pollux Mall Chadstone at least twice in the last three months. Data analysis was carried out using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method to test the validity, reliability, and relationships between variables in the research model. The results showed that mall positioning has a positive and significant effect on visitor satisfaction (β = 0.65, p <0.001), and visitor satisfaction has a significant effect on visitor loyalty (β = 0.72, p <0.001). In addition, mall positioning also directly affects visitor loyalty (β = 0.48, p < 0.01), but the effect becomes stronger when visitor satisfaction acts as a mediating variable. The results of the Sobel test confirm that this mediation effect is significant (Z = 4.21, p < 0.001). The conclusion of this study confirms that an effective positioning strategy can increase customer loyalty, especially through increasing visitor satisfaction. The implications of this study indicate that shopping center managers need to pay attention to factors that shape positioning, such as comfort, facilities, and brand perception, to retain customers in the long term.